Academic Writing: Critics of the Traditional EAP Approach - S. A. Sheypak (Moscow Polytechnic University, 2020)
Through the analysis of the positions taken in the discussion on Academic Writing, the article shows that the experience of Academic Writing adopted from Anglo-Saxon educational practices in many Russian universities is based on the traditional EAP (English for Academic Purposes) methods which have been systematically criticized for text-centricity and cultural universalism. The critical revision of the traditional EAP methods requires implementing a discourse analytical approach and cultural relativism in Academic Writing course. A review of critical studies on Academic Writing concludes that the criticism of the traditional EAP methods is developed on the basis of concepts worked in the Russian rhetoric tradition by researchers of the Bakhtin circle. The article points out that in the Russian educational context the EAP experience is to be implemented through a discourse analytical approach that has been adopted in the EAP practices in response to criticism. The concepts developed in the Russian rhetorical tradition are required to apply a discourse analytical approach in the Academic Writing course in Russian universities.